2015
DOI: 10.1016/j.vaccine.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy: Definition, scope and determinants

Abstract: The SAGE Working Group on Vaccine Hesitancy concluded that vaccine hesitancy refers to delay in acceptance or refusal of vaccination despite availability of vaccination services. Vaccine hesitancy is complex and context specific, varying across time, place and vaccines. It is influenced by factors such as complacency, convenience and confidence. The Working Group retained the term 'vaccine' rather than 'vaccination' hesitancy, although the latter more correctly implies the broader range of immunization concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

67
3,879
8
174

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,185 publications
(4,128 citation statements)
references
References 7 publications
67
3,879
8
174
Order By: Relevance
“…7 Among those who accept all vaccinations without any doubt (complete acceptance: corresponds to the highest proportion in the Apulian activity 50%) and those who completely refuse without uncertainty (total rejection: the lowest percentage, 15%), a heterogeneous group of uncertain people is also individuated. People belonging to this group nourish certainties toward some vaccinations and doubts about others and, consequently, decide to delay the vaccination uptake (35%).…”
Section: Discussionmentioning
confidence: 99%
“…7 Among those who accept all vaccinations without any doubt (complete acceptance: corresponds to the highest proportion in the Apulian activity 50%) and those who completely refuse without uncertainty (total rejection: the lowest percentage, 15%), a heterogeneous group of uncertain people is also individuated. People belonging to this group nourish certainties toward some vaccinations and doubts about others and, consequently, decide to delay the vaccination uptake (35%).…”
Section: Discussionmentioning
confidence: 99%
“…In Mozambique, information and education addressed to groups and individuals with low literacy is particularly relevant for women in rural areas, where literacy rates are low [21,22]. Through information and education, people can understand the significance and relevance of vaccines [3,18,19] which, in turn, may help to reduce vaccine hesitancy [23,24] and encourage people to contribute actively to the vaccination of their children. A recent study in Mozambique found that mothers’ understanding of how vaccines work is limited [20] and that their decision to take their child for vaccination is not based on clear knowledge of the mechanisms of vaccine protection.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 BC outbreak (9) and the recent Quebec outbreak in early 2015 (4) are examples of measles imported into a community where vaccinations were refused for religious/philosophical reasons. Those who refuse all vaccines represent only a small part of the continuum of vaccine hesitancy (10). Some parents may delay or be selective in providing all routine vaccinations for their children, resulting in individuals susceptible to infection (10).…”
Section: Immunization Promotion and Immunization Coverage Monitoringmentioning
confidence: 99%
“…Those who refuse all vaccines represent only a small part of the continuum of vaccine hesitancy (10). Some parents may delay or be selective in providing all routine vaccinations for their children, resulting in individuals susceptible to infection (10).…”
Section: Immunization Promotion and Immunization Coverage Monitoringmentioning
confidence: 99%